Assessing soil vulnerability in Petobo post-liquefaction zone, Palu, Central Sulawesi: A microzonation study utilizing microtremor measurements - Syamsuddin, Erfan; Maulana, Adi; Hamzah, Alimuddin; Irfan, Ulva Ria (Journal of Degraded and Mining Lands Management, 2024)
On September 28, 2018, a 7.5 Richter magnitude earthquake struck the Palu City neighborhood of Petobo. The tectonic activity along the Palu-Koro fault generated this earthquake, which resulted in soil liquefaction. The purpose of this study is to use microtremor measurements at 33 distinct places to investigate the properties of the soil layer after liquefaction. The obtained data was then evaluated utilizing Horizontal to Vertical Spectral Ratio (HVSR) methodologies such as Ground Shear Strength (GSS), amplification factor, and vulnerability index to determine the soil layer's properties and susceptibility. The dominant frequency ranges from 0.19 to 4.75 Hz, while the dominant period ranges from 0.21 to 5.17 seconds, according to the measurement results. According to these measurements, the silt layer varies between 5 and 30 m. GSS values in the 10-4 to 10-2 range indicate that soil cracking, subsidence, liquefaction, landslides, and compaction are likely. The soil vulnerability and amplification index values range from 2.36 to 4.37, respectively. These values show the potential level of danger, which might be low, medium, high, or extremely high. Peak ground acceleration varied from 299.52 to 301.52 gals, suggesting high to extremely high danger levels. The microzonation map created for this study is considered to be a useful resource for training disaster mitigation approaches and facilitating infrastructure development planning in the region.